Distance Measurement and Object Detection System Based On Ultrasonic Sensor and XBee - Seda Üstün Ercan; Mohammed Sufyan Mohammed (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2020)
In the past few years, research groups have focused on finding new solutions for objects detection in unknown and/or hazardous areas that can’t be accessed by humans, in order to create monitoring system that can ensure the safety and security of machine and humans operating in such areas. The aim of this study is to design and implement an object detection system based on XBee and ultrasonic sensor which is capable of detecting objects whether they are stationary or moving and obtain their exact location, direction and distance. This system is capable of detecting objects whether they are stationary or moving and obtain their exact location, direction and distance. It constantly monitors an area of limited range and reports to authorities, as soon as an object is detected two sets of alert can be activated at the same time. The first notification is an audible alert using a buzzer while the second one is a visual alert using personal computer screen with the help of graphical user interface. In addition to that, this system boasts many features such as low cost, tiny size, possible to carry and relocate with high efficiency and quality. Also it has a key advantage that is, this system doesn't require to be placed near the control room because it is able to monitor remote places and send the results wirelessly.